Menilai Perlindungan Konsumen pada Pasar Minyak Goreng di Indonesia: Pembelajaran dari Kasus Minyakita - Wibowo, Afrizal Mukti (CV. Social Politic Genius (SIGn), 2025)
The Minyakita case in Indonesia highlights the vulnerable position of consumers vis-à-vis business actors, particularly concerning the accuracy and reliability of product labeling. This issue underscores the ongoing risks consumers face in accessing goods conforming to package labels’ quality and standards. This research aims to analyze legal violations in the Minyakita case, specifically those related to misleading or non-compliant labeling practices, and to examine systemic weaknesses in the regulatory oversight of cooking oil distribution in the Indonesian market. Furthermore, this study compares Indonesia’s regulatory framework with Japan’s, especially regarding product labeling standards and the oversight of essential goods. The research explores loopholes and law enforcement challenges within Indonesia’s existing consumer protection framework, particularly concerning using state-owned brands and distributing public goods. It also presents a comparative analysis of Japan’s consumer protection regime, highlighting Japan’s stronger institutional oversight, crisis response mechanisms, and market discipline. Findings indicate that although Indonesia has a comprehensive legal foundation for consumer protection, its regulatory enforcement and institutional coordination remain weak. This research concludes by offering five policy recommendations to enhance transparency, public accountability, and consumer empowerment, fostering a fairer and more resilient essential commodities distribution system.